Sugary beverage intake and preclinical Alzheimer's disease in the community. Issue 9 (5th March 2017) - Pase, Matthew P.; Himali, Jayandra J.; Jacques, Paul F.; DeCarli, Charles; Satizabal, Claudia L.; Aparicio, Hugo; Vasan, Ramachandran S.; Beiser, Alexa S.; Seshadri, Sudha
Abstract: Introduction: Excess sugar consumption has been linked with Alzheimer's disease (AD) pathology in animal models. Methods: We examined the cross‐sectional association of sugary beverage consumption with neuropsychological ( N  = 4276) and magnetic resonance imaging ( N  = 3846) markers of preclinical Alzheimer's disease and vascular brain injury (VBI) in the community‐based Framingham Heart Study. Intake of sugary beverages was estimated using a food frequency questionnaire. Results: Relative to consuming less than one sugary beverage per day, higher intake of sugary beverages was associated with lower total brain volume (1–2/day, β ± standard error [SE] = −0.55 ± 0.14 mean percent difference, P  = .0002; >2/day, β ± SE = −0.68 ± 0.18, P  < .0001), and poorer performance on tests of episodic memory (all P  < .01). Daily fruit juice intake was associated with lower total brain volume, hippocampal volume, and poorer episodic memory (all P  < .05). Sugary beverage intake was not associated with VBI in a consistent manner across outcomes. Discussion: Higher intake of sugary beverages was associated cross‐sectionally with markers of preclinical AD.